Pengembangan Asesmen Kognitif dan Psikomotorik Agama Siswa - Salsabila Nur Imatul Adzillah; Tasman Hamami (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
This study aims to address the imbalance in Islamic Religious Education (PAI) assessment practices that predominantly emphasize cognitive mastery while neglecting the psychomotor aspect of students’ religious practices. The research seeks to develop an integrated assessment framework that measures both the intellectual understanding and behavioral application of Islamic teachings, thereby ensuring holistic evaluation and supporting character formation. This study employs a literature review method that systematically analyzes theoretical models, prior empirical findings, and best practices in the field of PAI assessment. Marzano’s Taxonomy is used as a conceptual lens to identify relevant cognitive assessment indicators, while psychomotor evaluation strategies are drawn from performance-based assessment theories and authentic assessment practices. The analysis reveals that Marzano’s framework effectively measures higher-order thinking and conceptual integration in religious learning. Meanwhile, psychomotor competencies can be validly assessed through performance tasks, direct observation, and self-assessment. Furthermore, integrating digital tools such as e-portfolios, mobile-based applications, and e-learning platforms enhances accuracy, transparency, and engagement in the assessment process. This conceptual model is limited by its reliance on secondary data and literature-based synthesis; therefore, further empirical validation is required to test its practical implementation across diverse educational settings. The study contributes a novel and comprehensive assessment model that bridges cognitive and psychomotor domains in Islamic Religious Education. It offers educators and policymakers a theoretically grounded and technologically adaptive framework to enhance the quality, relevance, and transformative impact of PAI assessment.